Investment-Led Growth in China. - Ahuja, Ashvin (IMF Working Papers., 2012)
Over the past decade, China's growth model has become more reliant on investment and its footprint in global imports has widened substantially. Several economies within China's supply chain are increasingly exposed to its investment-led growth and face growing risks from a deceleration in investment in China. This note quantifies potential global spillovers from an investment slowdown in China. It finds that a one percentage point slowdown in investment in China is associated with a reduction of global growth of just under one-tenth of a percentage point. The impact is about five times larger.